Association of height, foot length, and pubertal development in children aged 3–18: a cross-sectional survey in China - Wu, Hua-Hong; Zhang, Ya-Qin; Yu, Cheng-Dong; Yang, Li; Tao, Chen; Shu, Wen; Li, Tao; Huang, Guimin; Hou, Dongqing; Chen, Fang-Fang; Liu, Jun-Ting; Li, Shao-li; et al. (Frontiers in Public Health, 2024)
Objective: This study aims to analyze the growth patterns of height and foot length (FL) among Chinese children aged 3-18, and examine their association with puberty development.A cross-sectional survey was conducted in September 2022 in Beijing. Data was collected through questionnaire and on-site physical examinations. The growth patterns and velocity of Height and FL in different age groups were described, and their associations with puberty development was analyzed.Results: From an age perspective, the peak FL growth occurred between 9 and 11 years (boys is 11 years, girls is 9 years), while the peak Height growth occurred at 11~13 years for boys, and 9 ~11 years for girls. Additionally, boys and girls reach 99.0% of their final FL at the age of 14 and 13 respectively, while their Height reaches 99.0% of their final Height at the ages of 16 and 15 respectively. From the perspective of Tanner stage, the age of peak FL growth in boys coincides with the age of G2 stage, while in girls it occurs slightly earlier than the mean age of B2 stage. And the peak Height growth for both boys and girls occurred between Tanner 2 and 3 stages.Boys and girls reach their peak FL growth at 11 and 9 year old respectively, which were both 2 years earlier than their peak Height growth. And the peak FL growth occurs around the onset of puberty, while the peak Height growth occurs between Tanner 2 and 3 stages.